The effect of warm saltwater and warm water baths on pain, fatigue, sleep quality, and functional capacity in patients with rheumatoid arthritis: a randomized controlled study✰ - Okşan Aktaş; Ayşe Arikan Dönmez; Sevgisun Kapucu; Muhammet Çinar (BMC Complementary Medicine and Therapies)
Abstract Background Pain, fatigue, poor sleep quality and functional capacity are the most common symptoms in patients with rheumatoid arthritis. Complementary and integrative methods to be applied by nurses can be an essential strategy in successfully managing these symptoms. The purpose of this study was to examine the effects of warm salt water and warm water baths applied to the hands and feet on pain, fatigue, sleep quality and functional capacity in patients with rheumatoid arthritis. Methods This three-arm and prospective randomized controlled study fifty-four patients were randomly assigned to three groups (warm salt water: 18; warm water: 18; control: 18). Data were collected using the Visual Analog Scale, Bristol Rheumatoid Arthritis Fatigue Multidimensional Questionnaire, Disease Activity Score 28, Pittsburgh Sleep Quality Index, and Health Assessment Questionnaire. The intervention groups received warm saltwater or warm water hand-foot baths for six weeks. In all three groups, the measurements were taken at the beginning of the study and at the end of the last bathing sessions. Data were analyzed with chi-square test, one-way ANOVA, paired sample t-test, and two-way mixed ANOVA with Bonferroni’s test. Results Two-way mixed ANOVA revealed significant Group × Time interactions for pain (F = 9.736, p < 0.001, η² = 0.249), fatigue (F = 4.323, p = 0.013, η² = 0.158), and fatigue-related quality of life (F = 3.350, p = 0.043, η² = 0.116). Bonferroni post-hoc analyses indicated that both interventions (warm salt water and warm water) led to significant improvements in pain, fatigue, and sleep quality scores compared to the control group (p < 0.05), Notably, the most significant improvement in pain was observed in the warm saltwater group, while the most pronounced reductions in fatigue and fatigue-related quality of life were observed in the warm water group (p < 0.05). Although significant within-group improvements were observed in both intervention groups for sleep quality and only in the warm saltwater group for functional capacity (p < 0.05), no significant Group × Time interactions were found for either outcome (p > 0.05). Conclusions The findings of this study confirmed that warm saltwater and warm water baths applied to the hands and feet improved pain, fatigue, and sleep quality in patients with rheumatoid arthritis. Additionally, warm saltwater baths significantly improved functional capacity. These interventions may serve as safe, accessible, and effective complementary methods for symptom management. Registration Retrospectively registered with the ClinicalTrials.gov (Ref. No: NCT05888220). (Registration Date: 24 May 2023).